Manajemen Sarana dan Prasarana di TK Al Fatah: Facilities and Infrastructure Management at Al Fatah Kindergarten - Rani Puspita Sari; Erni Munastiwi (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2025)
Management of facilities and infrastructure is an important component in early childhood education (PAUD). Adequate and well-managed facilities and infrastructure can support children's learning and development processes. The purpose of this research is to determine: (1) Planning of facilities and infrastructure, (2) Procurement of facilities and infrastructure, (3) Distribution of facilities and infrastructure, (4) Maintenance of facilities and infrastructure, (5) Inventory of facilities and infrastructure, (6) Elimination facilities and infrastructure, and (7) Evaluating facilities and infrastructure at Al Fatah Kindergarten. This research is qualitative research with the type of field research (field research),   with data collection techniques using observation, interviews and documentation methods. The research results show that: 1) Planning for facilities and infrastructure needs at Al Fatah Kindergarten is managed well and in accordance with school needs; 2) Procurement of facilities and infrastructure is always carried out according to the decision of the school principal; 3) Inventory is carried out once a year; 4) Distribution of facilities and infrastructure is carried out directly; 5) Maintenance of Facilities and Infrastructure is carried out in the short and long term; 7) Removal of Facilities and Infrastructure is carried out by looking at the condition of the goods, and if the goods are not suitable for use they will be deleted; 8) Evaluation is carried out by involving the student's parents.   ABSTRAK  Manajemen sarana dan prasarana merupakan salah satu komponen penting dalam pendidikan anak usia dini (PAUD). Sarana dan prasarana yang memadai dan terkelola dengan baik dapat mendukung proses pembelajaran dan pengembangan anak. Tujuan penelitian ini untuk mengetahui: (1) Perencanaan sarana dan prasarana, (2) Pengadaan sarana dan prasarana, (3) Pendistribusian sarana dan prasarana, (4) Pemeliharaan sarana dan prasarana, (5) Penginventarisasian sarana dan prasarana, (6) Penghapusan sarana dan prasarana, dan (7) Pengevaluasian sarana dan prasarana di TK Al Fatah. Penelitian   ini merupakan   penelitian   kualitatif  dengan jenis penelitian lapangan (field research),   dengan   teknik pengumpulan data menggunakan metode observasi, wawancara dan  dokumentasi. Hasil penelitian menunjukkan bahwa: 1) Perencanaan kebutuhan sarana dan prasarana di TK Al Fatah dikelola dengan baik dan sesuai dengan kebutuhan sekolah; 2) Pengadaan sarana dan prasarana selalu dilakukan sesuai keputusan kepala sekolah; 3) Inventarisasi dilakukan setiap tahun sekali; 4) Pendistribusian sarana dan prasarana dilakukan secara langsung; 5) Pemeliharaan Sarana dan Prasarana dilakukan dalam jangka pendek dan jangka panjang; 7) Penghapusan Sarana dan Prasarana dilakukan dengan melihat kondisi barang, dan jika barang tidak layak pakai akan dihapus; 8) Pengevaluasian dilakukan dengan melibatkan wali murid.